Cost-effectiveness of denosumab versus zoledronic acid for preventing skeletal-related events in the Czech Republic. (3rd August 2017) - Cristino, Joaquim; Finek, Jíndřich; Jandova, Petra; Kolek, Martin; Pásztor, Bálint; Giannopoulou, Christina; Qian, Yi; Brezina, Tomas; Lothgren, Mickael
Abstract: Aims: This study assessed the cost-effectiveness of the subcutaneous RANKL inhibitor, denosumab, vs the intravenous bisphosphonate, zoledronic acid, for the prevention of skeletal-related events (SREs) in patients with prostate cancer, breast cancer, and other solid tumors (OST) in the Czech Republic. Materials and methods: A lifetime Markov model was developed to compare the effects of denosumab and zoledronic acid on costs (including drug costs and administration, patient management, SREs, and adverse events), quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios from a national payer perspective. Different discount rates, time horizons, SRE rates, distributions, and nature (asymptomatic vs all SREs), and the inclusion of treatment discontinuation were considered in scenario analyses. The robustness of the model was tested using deterministic and probabilistic sensitivity analyses. Results: Across tumor types, denosumab was associated with fewer SREs, improved QALYs, and higher total costs over a lifetime. The incremental cost per QALY gained for denosumab vs zoledronic acid was 382, 673 CZK for prostate cancer, 408, 450 CZK for breast cancer, and 608, 133 CZK for OST. Incremental costs per SRE avoided for the same tumor type were 54, 007 CZK, 51, 765 CZK, and 94, 426 CZK, respectively. In scenario analyses, the results remained similar to baseline, when different discount rates and time horizons were considered. At a non-official willingness-to-pay threshold of 1.2 million CZK, the probabilities of denosumab being cost-effective vs zoledronic acid were 0.64, 0.67, and 0.49 for prostate cancer, breast cancer, and OST, respectively. Limitations: The SRE rates used were obtained from clinical trials; studies suggest rates may be higher in clinical practice. Additional evidence on real-world SRE rates could further improve the accuracy of the modeling. Conclusions: Compared with zoledronic acid, denosumab provides a cost-effective treatment option for the prevention of SREs in patients with prostate cancer, breast cancer, and OST in the Czech Republic.